Inventory Waste Management In Micro Scale-Food Industry - Alam, Asnawi Mangku; Farmaciawaty, Desy Anisya (IPTEK Journal of Proceedings Series, 2020)
Micro-businesses in the culinary industry often experience management constraints. Poor management leads to many losses and wastes, such as inventory waste that arises due to mismatch of production level with demand level. This research aims to learn how the micro-business conditions in the culinary industry in Bandung deal with the problem of inventory waste and find suitable methods to overcome the problem. To carry out the research, we conduct a mix method technique. Data were collected through interviews with respondents who involved in micro-scale culinary businesses in Bandung and also from sales reports of internal data from Yama, a micro-scale company engaged in the culinary business. We analyzed the data using a qualitative method and a single-period inventory model. From the research, we found that the micro-business condition in the culinary industry has currently run their waste inventory management based on intuition without a scientific approach. Also, to solve the wasted inventory problem, the single-period inventory model can reduce the amount of inventory waste and can be implemented. It can significantly increase Yama's opportunity to make a profit and decreasing the possibility of inventory waste due to unsold inventory